Duloxetine versus ‘active’ placebo, placebo or no intervention for major depressive disorder; a protocol for a systematic review of randomised clinical trials with meta-analysis and trial sequential analysis - Faiza Siddiqui (Systematic Reviews, 2021)
Abstract Background Major depression significantly impairs quality of life, increases the risk of suicide, and poses tremendous economic burden on individuals and societies. Duloxetine, a serotonin norepinephrine reuptake inhibitor, is a widely prescribed antidepressant. The effects of duloxetine have, however, not been sufficiently assessed in earlier systematic reviews and meta-analyses. Methods/design A systematic review will be performed including randomised clinical trials comparing duloxetine with ‘active’ placebo, placebo or no intervention for adults with major depressive disorder. Bias domains will be assessed, an eight-step procedure will be used to assess if the thresholds for clinical significance are crossed. We will conduct meta-analyses. Trial sequential analysis will be conducted to control random errors, and the certainty of the evidence will be assessed using GRADE. To identify relevant trials, we will search Cochrane Central Register of Controlled Trials, Medical Literature Analysis and Retrieval System Online, Excerpta Medica database, PsycINFO, Science Citation Index Expanded, Social Sciences Citation Index, Conference Proceedings Citation Index—Science and Conference Proceedings Citation Index—Social Science & Humanities. We will also search Chinese databases and Google Scholar. We will search all databases from their inception to the present. Two review authors will independently extract data and perform risk of bias assessment. Primary outcomes will be the difference in mean depression scores on Hamilton Depression Rating Scale between the intervention and control groups and serious adverse events. Secondary outcomes will be suicide, suicide-attempts, suicidal ideation, quality of life and non-serious adverse events. Discussion No former systematic review has systematically assessed the beneficial and harmful effects of duloxetine taking into account both the risks of random errors and the risks of systematic errors. Our review will help clinicians weigh the benefits of prescribing duloxetine against its adverse effects and make informed decisions. Systematic review registration PROSPERO 2016 CRD42016053931